A CO-OPERATIVE CLINICAL STUDY ON EFFECTS OF COMBINED TREATMENT WITH 5'-DFUR (FURTULON®) AND RADIATION - NYUUNOYA, Kouichirou; HADA, Yoshihiro; ONODA, Kouji; NISHIO, Masamichi; MAKINO, Masaoki; ASAKURA, Hideo; SAITOU, Akio; YAMADA, Tsunehisa; TATSUNO, Ikuo (Japanese Journal of National Medical Services, 1991)
A co-operative study was carried out to evaluate effects of radiation alone and in combination with 5'-deoxy-5-fluorouridine (5'-DFUR), a 5-FU derivative. Patients with various cancers were treated. Nine national hospitals participated in the study and number of subjects amounted to 177 patients. The results indicated that no significant differences were observed between the patients treated with either therapies based on local effects but such excellent effects were obtained in the patients treated with the combination therapy especially in patients with breast cancer metastases, recurrent cancers, local effects and survival rates. Furthermore, cases of esophageal cancers undergoing preoperative combination therapy of radiation at 52 or 54 Gy with 5'-DFUR demonstrated complete disappearance of the tumor cells. No severe side effects were observed.